Iran in the 21st Century - Houchang Hassan-Yari (International Institute of Islamic Thought, 2008)
This multidisciplinary study addresses a host of issues facing Iran. Through a comprehensive study of political, economic, cultural, social, and securityrelated questions, seventeen Iranian researchers tried to create a book that is, as Katouzian states in her preface, “likely to become a standard text for the relevant academic courses.” In an elaborate introduction, the editors paint a quick picture of events endured by the Iranian people during the twentieth century up to the advent of the Islamic Republic in 1979. Farideh Farhi examines the question of crafting a national identity as a national preoccupation in modern Iranian history. She points to the central role of a narrative reference that brings together and connects all Iranians. The second main point of her analysis is the ongoing tension between what she calls autocratic/theocratic/ arbitrary rule and democracy/chaos and Iran’s relationship with the outside world. Farhi studies three sets of discursive transformations to illustrate her main points: the transformation of the national question into an ethnic challenge, of the Islam/pre-Islam dichotomy into a confrontation between popular sovereignty and patrimonialism, and of how “Iran” sees itself in the world...